The Role Of Trade Unions In Health Protection And Provision Of Safe Working Conditions For Medical Workers. Part 2. Health care Workers' Trade Union Activities - N. N. Kamynina; T V. Grishina; P. O. Ramenskiy; A. L. Dashkova; A. O. Batsenko (Здоровье мегаполиса)
Introduction. Healthcare workers are an important part of national healthcare systems ensuring its sustainability. Thus, it is necessary to introduce state mechanisms aimed at protecting their health and ensuring safe working conditions. Moreover, protection of rights and interests of healthcare workers is a matter of social justice. International and national public organizations and especially trade unions of healthcare workers play an important role in dealing with these issues.The purpose of the study is to consider examples of trade union activities on health protection and provision of safe working conditions in a number of countries upon the data on health issues that experience medical specialists as well as factors influencing these issues.Materials and methods. A content analysis of the official Internet pages of trade union organizations and their reporting documents for 2015-2024 was performed. Also, such methods as analysis, synthesis, secondary analysis and systematization of data were used.Results. Around the world, healthcare workers face occupational risks of infectious diseases, and are constantly exposed to various types of biological and non-biological hazards due to their working conditions, which are considered unsafe. Even cases of ill-treatment, threats, attacks or insults during the performance of professional duties are documented. Therefore, protection of health and safety of medical professionals, as well as their social and labor rights and interests is one of the main areas of trade unions as public organizations created on the initiative of healthcare workers.